2013
DOI: 10.1074/jbc.m113.510354
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 (SIRT3) Protein Regulates Long-chain Acyl-CoA Dehydrogenase by Deacetylating Conserved Lysines Near the Active Site

Abstract: Background: Reversible lysine acetylation regulates the fatty acid oxidation enzyme long-chain acyl-CoA dehydrogenase (LCAD). Results: Residues Lys-318 and Lys-322 are responsible for these effects. Conclusion: Acetylation of Lys-318/Lys-322 alters the conformation of the LCAD active site. Sirtuin 3 (SIRT3) deacetylates these lysines and restores function. Significance: Acetylation of LCAD Lys-318/Lys-322 can disrupt fatty acid oxidation and contribute to metabolic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 38 publications
6
115
0
Order By: Relevance
“…These data support the evidence showing increased fatty acid oxidation in the presence of excess fat and mitochondrial protein acetylation (8,9). Contrasting studies also show that the direct deacetylation of lysine residues on the fatty acid oxidation enzymes themselves can activate metabolic activity (5,6). Whether this reflects differential regulation of the same metabolic pathway at the levels of protein folding and enzyme activity is an intriguing concept that requires clarification.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These data support the evidence showing increased fatty acid oxidation in the presence of excess fat and mitochondrial protein acetylation (8,9). Contrasting studies also show that the direct deacetylation of lysine residues on the fatty acid oxidation enzymes themselves can activate metabolic activity (5,6). Whether this reflects differential regulation of the same metabolic pathway at the levels of protein folding and enzyme activity is an intriguing concept that requires clarification.…”
Section: Discussionsupporting
confidence: 66%
“…On one hand, the mitochondrial sirtuin SIRT3 targets numerous enzymes involved in fat oxidation. Here SIRT3 deacetylates and activates long-chain acylCoA dehydrogenase and medium-chain acyl-CoA dehydrogenase (MCAD) 3 (5,6). In parallel, under dietary restricted conditions, multiple fatty acid oxidation enzymes show increased lysine residue deacetylation in control versus SIRT3 knockout mice, and SIRT3 null mice have increased accumula-tion of acylcarnitines, a finding consistent with reduced fat oxidation (7).…”
mentioning
confidence: 54%
“…However, both enzymatic assays are reported to provide comparable results in medium-chain acylCoA dehydrogenase-deficient patients (24). On the other hand, some specific acetylation sites are shown to change the activity by modulating the conformation of the LCAD active site (2). This suggests that the impact of LCAD acetylation on its activity is, at least in part, due to a site-specific manner, and, as such, the discrepant findings between acetylation and fatty acid ␤-oxidation might be explained by the difference in specific acetylation site controlling metabolic enzymes.…”
Section: H354mentioning
confidence: 97%
“…3B). Our previous work using chemically acylated proteins as substrates for recombinant sirtuins has shown that SIRT3 and SIRT5 have highly specific target sites and will not deacylate lysine residues indiscriminately (1,16). Therefore, we used our succinyl-CoA-treated membrane protein fraction as substrate for recombinant SIRT5 to unveil potential target proteins/pathways.…”
Section: Sirt5 Counteracts Succinylation Of Mitochondrial Membrane Prmentioning
confidence: 99%